Topography of somatostatin gene expression relative to molecular progenitor domains during ontogeny of the mouse hypothalamus - Nicanor eMorales-Delgado; Nicanor eMorales-Delgado; Nicanor eMorales-Delgado; Paloma eMerchan; Sylvia M Bardet; José L E Ferran; Luis ePuelles; Carmen eDiaz; Carmen eDiaz (Frontiers Media S.A., 2011)
The hypothalamus comprises alar, basal and floor plate developmental compartments. Recent molecular data support a rostro-caudal subdivision into rostral (terminal) and caudal (peduncular) halves. In this context, the distribution of neuronal populations expressing somatostatin (Sst) mRNA was analyzed in the developing mouse hypothalamus, comparing with the expression pattern of the genes Orthopedia (Otp), Distal-less 5 (Dlx5), Sonic Hedgehog (Shh) and Nk2 homeobox 1 (Nkx2.1). At embryonic day 10.5 (E10.5), Sst mRNA was first detectable in the anterobasal nucleus, a Nkx2.1-, Shh- and Otp- positive basal domain. By E13.5, nascent Sst expression was also related to two additional Otp-positive domains within the alar plate and one in the basal plate. In the alar plate, Sst-positive cells were observed in rostral and caudal ventral subdomains of the Otp-positive paraventricular complex. An additional basal Sst-expressing cell group was found within a longitudinal Otp-positive periretromamillary band that separates the retromamillary area from tuberal areas. Apart of subsequent growth of these initial populations, at E13.5 and E15.5 some Sst-positive derivatives migrate tangentially into neighboring regions. A subset of cells produced at the anterobasal nucleus disperses ventralwards into the shell of the ventromedial hypothalamic nucleus and the arcuate nucleus. Cells from the rostroventral paraventricular subdomain reach the suboptic nucleus, whereas a caudal contingent migrates radially into lateral paraventricular, perifornical and entopeduncular nuclei. Our data provide a topologic map of molecularly-defined progenitor areas originating a specific neuron type during early hypothalamic development. Identification of four main separate sources helps to understand causally its complex adult organization.